Survival of HT29 Cancer Cells Is Affected by IGF1R Inhibition via Modulation of Self-DNA-Triggered TLR9 Signaling and the Autophagy Response - Ferenc Sipos; Bettina Bohusné Barta; Ágnes Simon; Lőrinc Nagy; Titanilla Dankó; Regina Eszter Raffay; Gábor Petővári; Viktória Zsiros; Barnabás Wichmann; Anna Sebestyén; Györgyi Műzes (Frontiers Media S.A., 2022)
Purpose: In HT29 colon cancer cells, a close interplay between self-DNA-induced TLR9 signaling and autophagy response was found, with remarkable effects on cell survival and differentiation. IGF1R activation drives the development and malignant progression of colorectal cancer. IGF1R inhibition displays a controversial effect on autophagy. The interrelated roles of IGF1R inhibition and TLR9/autophagy signaling in HT29 cancer cells have not yet been clarified. In our study, we aimed to investigate the complex interplay of IGF1R inhibition and TLR9/autophagy signaling in HT29 cells.Methods: HT29 cells were incubated with tumor-originated self-DNA with or without inhibitors of IGF1R (picropodophyllin), autophagy (chloroquine), and TLR9 (ODN2088), respectively. Cell proliferation and metabolic activity measurements, direct cell counting, NanoString and Taqman gene expression analyses, immunocytochemistry, WES Simple Western blot, and transmission electron microscopy investigations were performed.Results: The concomitant use of tumor-derived self-DNA and IGF1R inhibitors displays anti-proliferative potential, which can be reversed by parallel TLR9 signaling inhibition. The distinct effects of picropodophyllin, ODN2088, and chloroquine per se or in combination on HT29 cell proliferation and autophagy suggest that either the IGF1R-associated or non-associated autophagy machinery is "Janus-faced" regarding its actions on cell proliferation. Autophagy, induced by different combinations of self-DNA and inhibitors is not sufficient to rescue HT29 cells from death but results in the survival of some CD133-positive stem-like HT29 cells.Conclusion: The creation of new types of combined IGF1R, autophagy, and/or TLR9 signaling inhibitors would play a significant role in the development of more personalized anti-tumor therapies for colorectal cancer.